Digital transformation and hospitality management competencies: Toward an integrative framework. (April 2022) - Busulwa, Richard; Pickering, Mark; Mao, Iris
Abstract: Digital transformation requires hospitality and tourism organizations to build and sustain digital business capabilities such as digital customer engagement, digital customer experience management, digital innovation, digital leadership, and others. These organization digital business capabilities, in turn, require corresponding digital transformation and digital business management competencies. This has important implications for required hospitality management competencies. We identify the specific digital transformation and digital business management competencies required by hospitality managers. Then, given a disconnect between these competencies and previously identified hospitality management digital technology competencies, we propose a framework integrating digital transformation and digital business management competencies with previously identified digital technology competencies required by hospitality managers. The proposed framework has important implications for curricula design and managerial practice. These implications as well as future research ideas are discussed. Highlights: Hospitality and tourism managers need to effectively participate in their organizations' digital transformation agendas. To do so, they require corresponding digital transformation and digital business-related competencies. The specific digital transformation and digital business-related competencies they require are identified. A framework is proposed for integrating and enhancing understanding of required managerial digital technology competencies.